Augmenting the Sense of Attachment Security in Group Contexts: The Effects of a Responsive Leader and a Cohesive Group. Issue 2 (3rd April 2017) - Mikulincer, Mario; Shaver, Phillip R.
ABSTRACT: According to attachment theory, the availability of caring, supportive relationship partners, beginning in infancy, is important to developing a sense of attachment security, which in turn fosters the development of stable self-esteem, constructive coping strategies, maintenance of mental health, and formation of mutually satisfying relationships throughout life. In this article, we move beyond the well-researched correlates of attachment security and the laboratory priming of security-enhancing mental representations to propose a broader group-related model of psychological change. According to this model, repeated interactions with responsive and supportive leaders and cohesive groups beneficially alter a person's attachment patterns and psychological functioning. We review prospective longitudinal findings showing that being involved in a relationship with a responsive and supportive leader or a cohesive and supportive group creates long-term beneficial changes in attachment-related cognitions and feelings and in broader psychological functioning. The findings provide strong support for Bowlby's ideas about the plasticity of the attachment system across the life span and the growth-enhancing consequences of responsive leaders and cohesive groups.